Analisis Pengaruh Pemberdayaan Terhadap Komitmen Perawat Dalam Kualitas Layanan Pada RSUD Dr.M.Haulussy Ambon - Tanihattu, Maudy Marla (Arthavidya Jurnal Ilmiah Ekonomi, 2012)
Health Services Industry, in particular hospitals, is rapidly growing characterized by the increasing of medical facilities and services provided to the public as consumers. Nurses are individuals who directly cope with the consumers in providing medical services. This purposes of the study was to distinguish the impact of nurses’ empowerment on their commitment in services quality.The analysis was conducted on each variable to examine the relationship among variables by observing the value of chi-square test and significance value. The sample was taken were the nurses at RSUD Dr.M.Haulussy Ambon with total sample of 109 respondents. The instrument used in the analysis was chi-square test.The results confirms that the hypotheses in this study are supported. It means that the correlation of nurses ‘ empowerment with nurses’ commitment in services quality has positive influence and statistically significant.Keywords : Nurses’ Empowerment, Nurses’ commitment in services quality